2008
DOI: 10.1590/s1806-83242008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the effect of two chlorhexidine mouthrinses on plaque accumulation and gingival bleeding

Abstract: The aim of the present study was to evaluate the effect of two chlorhexidine rinsing solutions (0.12% and 0.2%) on plaque and gingival bleeding. Ten dental students participated in this double-blind, cross-over study, rinsing twice a day, for one minute, with each one of the tested solutions for fourteen days. A wash-out period of one week between treatments was observed. In order to assess gingival bleeding, the van der Weijden et al. 1 (1994) index was used. The plaque indexes used were those of Quigley, He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 21 publications
(19 reference statements)
3
19
1
1
Order By: Relevance
“…This shows that the individuals with a higher plaque score at baseline also had more marked gingival inflammation Thus, the present study suggests an association between plaque and gingival status. This finding is in agreement with the study by Neto C et al [27]. In which they found that increase in plaque score is associated with increased gingival inflammation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This shows that the individuals with a higher plaque score at baseline also had more marked gingival inflammation Thus, the present study suggests an association between plaque and gingival status. This finding is in agreement with the study by Neto C et al [27]. In which they found that increase in plaque score is associated with increased gingival inflammation.…”
Section: Discussionsupporting
confidence: 94%
“…This can be explained by the fact that combined use of mechanical and chemical oral hygiene aids is useful in reducing gingival bleeding as well as gingival inflammation. Group 3 was also found to be effective in reducing gingival scores in the individuals which is similar to the findings of Najafi M et al [26], Neto C et al [27] and J. L Lyes et al [28]. This is suggestive of the fact that the chemical agents are superior to mechanical means in reducing gingival inflammation.…”
Section: Discussionsupporting
confidence: 86%
“…Even in a low concentration (0.05%) as suggested by Barnabé et al (9) for complete dentures, sodium hypochlorite was capable of causing surface damage (Fig. 2), in accordance with most of the works found in the literature, which do not indicate its use in prosthesis with metallic components (15,20,21). Although the manufacturer of the Medical Interporous tablets has indicated its use in metallic structures, this tablet led to surface corrosion of the evaluated metallic alloys.…”
Section: Discussionsupporting
confidence: 72%
“…In the acid category, a citric acid-based tablet recently introduced in the market (Medical Interporous) was slected, with the indication of use in metallic components with no deleterious effects. Cepacol and Periogard rinsing solutions were also evaluated for their antimicrobial effects (18)(19)(20). Distilled water was used as control.…”
Section: Discussionmentioning
confidence: 99%
“…Similar study design was followed in a clinical trial where the subjects continued to exercise their regular non-supervised, self-performed plaque control measures. [3] Carlos Alfredo Franco Neto et al .,[27] stated that there is no difference in the efficacy of chlorhexidine between 0.12 to 0.2% and the former concentration leads to less staining of teeth. Hence, in this study 0.12% concentration was used since the study duration was 4 weeks.…”
Section: Discussionmentioning
confidence: 99%